Recovery of dehydrogenase enzymes activities Heteropneustes fossilis (Bloch) exposed to sublethal levels of mercury - James, R; Sampath, K; Devakiamma, G; Pattu, V Jancy (Indian Journal of Fisheries, 2011)
The impact of sublethal levels of mercury on the activities of succinatedehydrogenase (SDH) and Glyceroldehyde dehydrogenase (GDH) enzymes indifferent tiBsues of Heterapneustes tassilis were studied. Recovery of enzymeactivities were also assessed. Sublethal concentrations of mercury inhibitedthe SDH activity and enhanced the GDH activity in all tested tissues; theinhibition and enhancement were concentration dependent. This suggests thesuppression of oxidative metabolism and triggering of anaerobic metabolismto derive energy during metal stress. Metal exposed animals when shifted tometal impoverished water, showed recovery in the activity of both enzymes,however, it was not complete.